PENGARUH PUPUK KOMPOS MABAR DAN NPK YARA MILA 16:16:16 TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN SELADA (Lactuca sativa L.) - Donatus Dahang; Lyndon Parulian Nainggolan; Muhammad Fauzan Zulazmi; Junius Firmanta Tarigan (JURNAL AGROTEKNOSAINS, 2023)
Research has been carried out using Mabar Compost and NPK Yara Mila 16:16;16 on lettuce (Lactuca Sativa L.). The aim of the study was to determine the effect of Mabar Compost Fertilizer, the effect of NPK Yara Mila 16:16:16, and the effect of the interaction between the two types of fertilizer on the growth and yield of lettuce plants. The study used a factorial randomized block design consisting of two factors. Factor I: Dosage of Mabar Compost with the symbol "K", namely K0: 0 Control (without treatment), K1: 350 grams/plot, K2: 550 grams/plot, and K3: 750 grams/plot. Factor II: Dosage of NPK fertilizer with the symbol "P", namely P0: 0 Control (without treatment), P1: 18 grams/plot, P2: 24 grams/plot, P3: 30 grams/plot. The results showed that Mabar Compost Fertilizer and NPK Fertilizer had no significant effect on the height and number of leaves of lettuce plants. Mabar Compost Fertilizer had a significant effect on the yield weight of fresh lettuce plants. The average yield weight of plants affected by compost was K0 (109.4 gr), not significantly different from K1 (120.2gr) but significantly different from K2 (125.4 gr) and K3 (165.2 gr). No interaction was found between the type of fertilizer and the dose of fertilizer on the research parameters.